Magnetoelastic properties in polycrystalline Fe-Pd based ferromagnetic shape memory alloys. (March 2019) - Sofronie, M; Popescu, B; Crisan, AD; Lupu, AR; Tolea, F; Valeanu, M
Abstract: Two series of Mn substituted Fe-Pd ferromagnetic shape memory ribbons were studied by X-ray diffraction, calorimetric and thermo-induced strain measurements. Linking the structural, magnetic and thermal expansion analysis on pristine ribbons and those subjected to different subsequent thermal treatments, highlights the role of substitution and of heat treatment of the martensitic transformation (MT). The melt–spinning technique removes the precipitation of undesirable b.c.t. irreversible phase and the addition of Mn, as a third alloying element, promotes the stabilization of the f.c.t. martensite. The linear thermal expansion measurements with and without static magnetic field provide information on the easy magnetization axis in the martensitic structure. Preliminary in vitro cytotoxicity tests generally indicate no toxicity or a tendency towards cell proliferation induced by the tested materials.